2019
DOI: 10.1001/jamanetworkopen.2019.2745
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Accelerometer-Measured Light-Intensity Physical Activity With Brain Volume

Abstract: Key Points Question Is light-intensity physical activity associated with brain volume? Findings In this community-based cohort study of 2354 participants, each additional hour spent in light-intensity physical activity was associated with larger brain volume, equivalent to approximately 1.1 years less brain aging. Achieving 10 000 or more steps per day was associated with higher brain volume compared with those achieving fewer than 5000 steps per day. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 56 publications
7
104
2
2
Order By: Relevance
“…The tendency for more sensory motor activity in PE might reflect more attention to the body during exercise and is also consistent with previous findings using relaxation training (Tang et al, 2009;Tang, 2017). These results are consistent with recent findings that continuous light-intensity physical activity contributes to brain plasticity (Spartano et al, 2019).…”
Section: Central Nervous Systemsupporting
confidence: 94%
“…The tendency for more sensory motor activity in PE might reflect more attention to the body during exercise and is also consistent with previous findings using relaxation training (Tang et al, 2009;Tang, 2017). These results are consistent with recent findings that continuous light-intensity physical activity contributes to brain plasticity (Spartano et al, 2019).…”
Section: Central Nervous Systemsupporting
confidence: 94%
“…In addition to ECG, wearable devices are also useful to monitor the level of activity of people. A study that analyzed data from 2354 prospective cohorts in the United States confirmed the relationship between activity and brain volume, indicating that mild exercise is associated with larger brain volume [28]. An additional one hour of mild exercise in a day can reduce the age of the brain by 1.1 years.…”
Section: Recent Cases Of Application Of Ai To Biosignals In Medicinementioning
confidence: 93%
“…78,79 Individuals who exercise the most may have a larger total brain volume, with the incremental physical activity having different effects on multiple brain regions. 80 As previously mentioned, the amelioration of hemodynamic responses may be at the basis of brain modifications upon physical exercise, extraordinarily mirroring cardiovascular improvements and the acquisition of a general physical and psychological health.…”
Section: The Reciprocal Relationship Between Physical Fitness and Neumentioning
confidence: 94%